Babri Mosque: a historic bone of contention - Islam, Arshad (Blackwell Publishing, 2007)

(untitled)
Since 1855, the Babri Mosque in Ayodhya has been the source of sporadic clashes between Hindus and Muslims. After a thorough scrutiny of the available historical literature on the Mosque, this article argues that to regard it as the birthplace of the Hindu deity Rama is untenable and the notion was actually put into circulation by British colonial officials to serve British interests in the Indian subcontinent. Successive colonial administrations tried to strengthen their grip on South Asia by playing off one group against another in the name of caste, race, and, most importantly, religion. The ongoing Hindu-Muslim conflict in India is largely the outcome of British policies. With their agenda of 'divide and rule' that aimed at consolidating their hold over the subcontinent the British tried to create a huge chasm between Hindus and Muslims. They labelled Muslims as the oppressors and Hindus as the oppressed, working to gain the support of the Hindu masses by provoking their hatred of the Muslims; and they strongly backed their religious and other claims in a vast amount of biased literature. It was with this colonial agenda that they endorsed the Hindu claim to the site of the Babri Mosque.